Controlled Cracking of Large Size Concrete Structures by a Steam Pressure Cracking Agent. (2021) - Kamiya, Osamu; Suzuki, Kaito; Okuyama, Etsushi; Kojima, Naoya; Nanao, Jyunpei; Ito, Shinichi; Takahashi, Mamoru; Miyano, Yasuyuki; Murata, Kenji; Kazumi, Takashi; Maisawa, Arata; Nakatsu, Masanobu; et al.
No abstract available